Penguatan Nilai Masyarakat Bugis Macca na Lempu dalam Perspektif Pendidikan Karakter - Hamsah Hamsah; Romi Mesra (Lembaga Penelitian dan Pengabdian Universitas Negeri Manado, 2022)
Character education is the main concern and benchmark for educational success. Until now the concept and results of the implementation of character education have not been fully successful. Therefore, one of the objectives of this research is to examine the strengthening of the values of the Bugis community regarding macca na lempu in a character education perspective. Through the literature study conducted, it was found that the values of macca and lempu are an inseparable unit. The strengthening strategy can be carried out through learning, exemplary, strengthening and habituation.